TINDAKAN HUKUM TERHADAP PELAKU PENYEBARAN VIRUS KOMPUTER MELALUI E-MAIL (CYBER SPAMMING) BERDASARKAN KETENTUAN TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Hassanah, Hetty (Fakultas Hukum Universitas Komputer Indonesia, 2023)
The purpose of this study is to find out and analyze the legal actions that can be taken against perpetrators of spreading komputer viruses via email (cyber spamming) based on applicable law. The research is descriptive analytical, using a normative juridical approach, through laws and regulations related to information technology, then the data obtained are analyzed in a qualitative juridical manner. The results of the study show that the act of spreading komputer viruses via email (cyber spamming) can be applied to the provisions of Article 30 paragraph (2) in conjunction with Article 46 paragraph (2) of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions, provided that it must be proven that the actions taken by the perpetrators fulfill the subjective and objective elements of the article. The conclusion obtained from this research is that the act of spreading komputer viruses via email (cyber spamming) is a violation of the law as regulated in the Electronic Information and Transaction Law and the perpetrators must be given legal sanctions according to applicable regulations. The impact of this research is that the government must always supervise the development of information technology and violations that occur so that they are always accommodated by existing regulations, besides that the public must always be careful in using internet-based information media.